The effects of protectionism on the exports of the trade partners: A composite index - Emmanouil Karakostas (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: This study constructs a quantitative tool that can interpret the effects of trade protectionism on trading partners. Design/methodology/approach: Trade protectionist policies are a crucial phenomenon of international political economy. The existing literature has analyzed the consequences, causes, and effects of trade protectionist policies. A principal aspect of the present study is the diverse consequences of the operation of protectionism on trading partners. The central question is this: exactly in what way are the exports of trading partners influenced by a trade "war"? The methodology utilized is the composition of a Composite Index (CI). Findings: The analysis of this paper showed that the country's participation in international trade flows, economic and commercial strength and symmetrical or asymmetric interdependence with the countries involved on trade protectionism are the important aspects that determine the significance of the protectionist effects. Research limitations/implications: The composite index signifies the amount of the impact and not the kind. Actually, a state can have an unimportant influence on the trade protectionist policies of two of its trading partners, but this consequence could have an undesirable connotation. The reason is that the index does not examine the entire exports of a country, but the proportion of trade interconnections. Originality/value: The composite index is crucial for interpreting the effects of a phenomenon of global political economy.
Keywords: F10; F14; F40; 330; Protectionism; Global trade; Exports; Composite Index